O desenvolvimento profissional docente na voz dos professores alfabetizadores - Pascotto, Alessandra Daniele [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This dissertation focuses on the issue of Teacher Professionalism. Presents research on the approaches given by literacy teachers, their initial training and contributions to building their teaching knowledge (theoretical and practical).With the purpose of providing grants for public policies for teacher education, this study analyzes how important the initial and continuing training for literacy teachers. Participated in the survey in 2013, 39 teachers, one from each school, which corresponds to approximately 30% of effective literacy teachers, who taught in the 1st year of elementary school in public schools in a city in the state of São Paulo. The instruments used for data collection are: semi-structured, recorded and transcribed individual interviews and analysis of documents relating to continuing education activities offered to literacy by the Municipal Secretary of Education for the period 2010 to 2013. In 2010, work began on the deployment in the city of Elementary School 9 years according to official regulations. The data obtained are analyzed in the light of the theoretical contributions of authors such as Micotti (1998, 2004, 2009, 2012), Tardif (2002, 2006), Tardif and Lessard (1998); Schon (1983); Gatti (2009) and others, involving discussion and reflection about the professionalization of the teaching profession, the professional development of teachers and the construction of teaching knowledge, in particular knowledge needed to literacy teacher. The results indicate that literacy teachers while acknowledging the importance of initial training it is insufficient for the practice of teaching, particularly in relation to the teaching of theoretical and practical knowledge related to the teaching and learning of literacy. Reaffirm the results of previous research to show that when this main source of knowledge of the construction of the teaching practices ... (Complete abstract electronic access below)

Esta dissertação focaliza a questão da Profissionalidade Docente. Apresenta pesquisa sobre os enfoques dados pelos professores alfabetizadores, à sua formação inicial e às contribuições para a construção de seus saberes docentes (teóricos e práticos). Com a finalidade de oferecer subsídios para as políticas públicas de formação de professores, este estudo analisa qual a importância da formação inicial e continuada para os professores alfabetizadores. Participaram da pesquisa, em 2013, 39 docentes, um de cada unidade escolar, o que corresponde a aproximadamente 30% dos alfabetizadores efetivos, que lecionavamno 1º ano do Ensino Fundamental em escolas municipais de uma cidade do interior do Estado de São Paulo. Os instrumentos utilizados para coleta de dados são: entrevistas individuais semiestruturadas, filmadas e transcritas, bem como análise de documentos referentes às atividades de formação continuada oferecida aos alfabetizadores pela Secretaria Municipal da Educação no período de 2010 a 2013. Em 2010, iniciou-se a implantação no município do Ensino Fundamental de 9 anos de acordo com legislação oficial em vigor. Os dados assim obtidos são analisados à luz das contribuições teóricas de autores tais como Micotti (1998, 2004, 2009, 2012), Tardif (2002, 2006), Tardif e Lessard (1998); Schon (1983); Gatti (2009) e outros, que envolvem a discussão e reflexão a respeito da profissionalização docente, da profissionalidade docente, do desenvolvimento profissional docente e da construção dos saberes docentes, em especial dos saberes necessários ao professor alfabetizador. Os resultados permitem afirmar que os professores alfabetizadores apesar de reconhecerem a importância da formação inicial ela é insuficiente para o exercício do magistério, principalmente no que se refere ao ensino dos saberes teóricos e práticos relacionados aos ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Professores - Formação; Políticas públicas; Professores alfabetizadores; Alfabetização; Ensino fundamental; Teachers, Training of; São Paulo (Estado)